2023
DOI: 10.7554/elife.82516
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated evolution at amino acid sites of SARS-CoV-2 spike

Abstract: SARS-CoV-2 has adapted in a stepwise manner, with multiple beneficial mutations accumulating in a rapid succession at origins of VOCs, and the reasons for this are unclear. Here, we searched for coordinated evolution of amino acid sites in the spike protein of SARS-CoV-2. Specifically, we searched for concordantly evolving site pairs (CSPs) for which changes at one site were rapidly followed by changes at the other site in the same lineage. We detected 46 sites which formed 45 CSP. Sites in CSP were closer to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…The results suggest that the BA.2.86 variant may have evolved to accumulate convergent immune escape mutations while exploiting potential synergistic epistatic effects of a selected group of hotspots R403K and R493Q to enable sufficient ACE2-binding capability. Several lines of evidence indicated that the observed coordination of evolution at different sites can be due to epistatic, rather than random selection of mutations. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the BA.2.86 variant may have evolved to accumulate convergent immune escape mutations while exploiting potential synergistic epistatic effects of a selected group of hotspots R403K and R493Q to enable sufficient ACE2-binding capability. Several lines of evidence indicated that the observed coordination of evolution at different sites can be due to epistatic, rather than random selection of mutations. , …”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence indicated that the observed coordination of evolution at different sites can be due to epistatic, rather than random selection of mutations. 124,125 MM-GBSA Computations of the Binding Free Energies for the Omicron RBD BA.2 and BA.2.86 RBD-ACE2 Complexes. Using the conformational equilibrium ensembles obtained from MD simulations, we computed the binding free energies for the Omicron RBD BA.2 and BA.2.86 RBD complexes with ACE2 using the MM-GBSA method.…”
Section: Mutational Scanning Heatmaps Of the Ba2 And Ba286 Rbd Residu...mentioning
confidence: 99%
“…Remarkably, convergent evolution seen in these examples allowed for the improved or neutral binding affinity changes and immune escape. Several lines of evidence indicated that the observed coordination of evolution at different sites is largely due to epistatic, rather than random selection of mutations [140]. Epistatic interactions between mutations add substantial complexity of their adaptive landscapes are believed to play an important role in the virus evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all predictions were made before the actual Omicron haplotypes emerged, at a cumulative frequency of 0. The Delta variant (B.1.617.2) serves as another example of multiple early predictions, as it becomes significantly dense in ten countries (F D des ∈ [15, 360] and F D prev ∈ [30,375]).…”
Section: Vocs/vois As Communities In Epistatic Networkmentioning
confidence: 99%